2022
DOI: 10.3390/math10020166
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Constitutionalization: Twitter Sentiment Analysis of the Chilean Constitutional Process through Bayesian Network Classifiers

Abstract: Constitutional processes are a cornerstone of modern democracies. Whether revolutionary or institutionally organized, they establish the core values of social order and determine the institutional architecture that governs social life. Constitutional processes are themselves evolutionary practices of mutual learning in which actors, regardless of their initial political positions, continuously interact with each other, demonstrating differences and making alliances regarding different topics. In this article, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…In summary, the stability or within-author consistency of sentiment scores was established in the tests presented earlier. Some studies have already used sentiment analysis to predict public mood and conduct opinion mining based on the polarity of emotions (positive or negative) (Albahli, 2022;Birjali et al, 2021;Neogi et al, 2021;Ruz et al, 2022). Martins et al (2021) even identified authors through polarity of emotions (positive or negative) based on the presence or absence of emotions such as anger, joy, and surprise, along with consideration of authors' categories (politicians and non-politicians).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the stability or within-author consistency of sentiment scores was established in the tests presented earlier. Some studies have already used sentiment analysis to predict public mood and conduct opinion mining based on the polarity of emotions (positive or negative) (Albahli, 2022;Birjali et al, 2021;Neogi et al, 2021;Ruz et al, 2022). Martins et al (2021) even identified authors through polarity of emotions (positive or negative) based on the presence or absence of emotions such as anger, joy, and surprise, along with consideration of authors' categories (politicians and non-politicians).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main advantages of using DBSCAN in SA is that it can handle datasets with varying [63], and it does not require the number of clusters to be specified in advance (like in the case of K-means). It can also identify clusters of reviews that have similar sentiments and are close together in the feature space.…”
Section: C) Density-based Spatial Clustering Of Applications With Noi...mentioning
confidence: 99%
“…Initially, Bayesian networks were built manually, but due to the large amount and constant increase of data, there was a need to develop algorithms to learn networks from data. Learning Bayesian networks from data has two components: (1) the structure of the networks and (2) the parameters (conditional probability tables) ( 38 ). The Bayesian network has the advantages of dealing with missing data and modeling the interdependence between two variables even when the relationship between them is unknown ( 39 ).…”
Section: Prediction Modelsmentioning
confidence: 99%